1977
DOI: 10.1254/jjp.27.667
|View full text |Cite
|
Sign up to set email alerts
|

Natriuresis of Fasting in Intact and Adrenalectomized Rats

Abstract: Abstract-Experimentswere carried out in an attempt to elucidate the mechanism of fasting-induced natriuresis in conscious rats. Female animals were given a low sodium diet and saline in a fixed concentration for at least three days, and deprived of food thereafter. The sodium balance significantly shifted to negative independently of potassium supply in intact rats. Such was also observed in the dexamethasone replaced, adrenalectomized rats and was not affected by further administration of aldosterone.In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The concentrations of Na and Cl in the male and female 40% groups were higher than those in the control group, when the urine volume was considered (Supplemental Table 2). Natriuresis has been shown to occur in humans during fasting (Schloeder and Stinebaugh, 1970;Sigler, 1975), and this has also been identified in fasted rats (Fitzgerald et al, 2001;Nohno et al, 1977). Although the mechanism underpinning natriuresis is not fully understood, it has recently been suggested to involve the sodium-glucose transporter 2 (SGLT-2) in the proximal tubules of the kidney.…”
Section: Evaluation Of the Urinalysis Datamentioning
confidence: 99%
“…The concentrations of Na and Cl in the male and female 40% groups were higher than those in the control group, when the urine volume was considered (Supplemental Table 2). Natriuresis has been shown to occur in humans during fasting (Schloeder and Stinebaugh, 1970;Sigler, 1975), and this has also been identified in fasted rats (Fitzgerald et al, 2001;Nohno et al, 1977). Although the mechanism underpinning natriuresis is not fully understood, it has recently been suggested to involve the sodium-glucose transporter 2 (SGLT-2) in the proximal tubules of the kidney.…”
Section: Evaluation Of the Urinalysis Datamentioning
confidence: 99%
“…It is said not to occur in rats (Van Liew, Eisenbach, Dlouha & Boylan, 1978) but this may reflect the very high levels of sodium frequently contained in rat diets (Michell, 1978); Nohno, Hayashi & Murayama (1977) have reported fasting natriuresis in rats on low sodium diets. Both human and animal studies generally involve complete food deprivation for periods ranging from 3-23 d whereas the present paper reports a very similar pattern of sodium excretion induced by a mild reduction of food intake for merely 48 h, with or without parallel restriction of drinking.…”
Section: Fasting Natriuresis and Other Aspectsmentioning
confidence: 99%
“…We have recently observed that fasting for one to four days resulted in the negative sodium balance in rats provided a low salt diet and saline (2). The fasting-induced natriuresis in the rat revealed two aspects, one dependent on the level of sodium intake, and the other not (3). The latter seems to be largely concerned with the negative value of sodium balance in the lower level of sodium intake maintained relatively constant.…”
mentioning
confidence: 98%